Implementation of the Gandoriah-Sunur Beach Tourism Destination Development Program as a Pariaman City Tourism Strategic Area (KSPK), West Sumatra Province, Indonesia - Nurul Fasdiah; Pratiwi Nurhascaryani; Mutia Rahmah (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2021)
The Tourism and Culture Department has made a program to develop the Gandoriah-Sunur Beach tourism destination as a Pariaman City Tourism Strategic Area (KSPK), West Sumatra Province, Indonesia. However, this program has been hampered by a lack of suitable facilities and infrastructure, tourism resources and funds, and a low level of promotion and investment. Therefore, this study aims to identify and analyze the implementation of the Gandoriah-Sunur Beach tourism destination development program as a Pariaman City Tourism Strategic Area (KSPK) in West Sumatra Province. The descriptive qualitative approach using the inductive method was employed, and the data collection was conducted through interviews, observation, and documentation techniques. Furthermore, purposive and snowball sampling approaches were used to identify the informants. Data collection techniques include condensation, presentation, and drawing conclusions. The results show that implementing the Gandoriah-Sunur Beach tourism destination development program as a Pariaman City Tourism Strategic Area (KSPK), West Sumatra Province, is not ideal, as evidenced by the non-linearity of standards with costs and the inefficient allocation of funds.